Determinan Keputusan Pembelian Produk UNIQLO di Karawang Pada Masa Pandemi COVID-19 - Nurul Aulia Dewi; Asep Muslihat (Peneliti.net, 2022)
Economic development also greatly affects the lifestyle of the people who tend to prioritize appearance, which supports the appearance by using products that already have quality and are known by the public. Products that already have a good brand image certainly also have product quality that matches the price offered by the company to consumers. Seeing the rapid growth of Fast Fashion Uniqlo both in the domestic market and in the global market, Uniqlo is considered a brandfast fashion that is quite successful in managing product quality and brand (brand image) well. In addition, it can be proven by a number of data from global top brands which shows that Uniqlo is ranked 4th competing with other well-known brands that previously entered the fashion field first. This research was conducted to determine the determinants in the decision to purchase Uniqlo products during the COVID-19 pandemic in Karawang. The research method used is associative research with a quantitative approach. The population in this study were students of Singaperbangsa Karawang University who had carried out uniqlo product purchase activities. The total sample of this study was 96 respondents who had shopped at uniqlo Karawang branch. From the results of the study, a coefficient of determination (R Square) of 0.565 was obtained, which means that the influence of brand image and product quality as a determinant of purchasing decisions was 75.1%.